Analysis of the Role of Teachers in Increasing Citizenship Awareness Through Civics Learning in Elementary Schools - Sinaga, Bernike; Pandiangan, Cyntia Olivia; Barus, Destita Br; Sihombing, Dina Putrision (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This study investigates the role of teachers in increasing students' civic awareness through Pancasila and Citizenship education (PPKn) provided in elementary schools. The research was carried out at SDN 060939, Jl. Turi Timbang Deli Medan Amplas District, Medan, The main aim of this research is to identify the approaches and approaches used by teachers in teaching citizenship concepts. In addition, this research will also investigate how this impacts students' understanding and perceptions of civic values. Qualitative case studies were conducted through classroom observations, in-depth interviews with teachers and students, and analysis of curriculum documents. The research results show that teachers, through interactive learning, group discussions, and community-based projects, play an important role in increasing students' civic awareness. Apart from that, parental involvement and support from the school environment also contribute greatly to the quality of PPKn learning. This research emphasizes how important it is for teachers to receive ongoing training to improve their pedagogical skills.Besides that, limited time, availability of resources, and variations in student understanding are problems for teachers when teaching Civics. According to this research, schools and governments must provide better support to teachers through training, comprehensive open materials, and good learning environments. Thus, Civics learning is expected to increase students' civic awareness.